Six-Membered Ring Systems: With O and/or S Atoms - Santos, Clementina M.M. (2017)
In 2016, the large variety of publications focused on the synthesis of O- and S-6-membered ring systems highlights the importance and popularity of these heterocyclic compounds. Reviews on natural products covered the origins and medicinal use of avermectins (16AGE10190), discovery, isolation, characterization and application of artemisinin (16AGE10210), biosynthesis of fungal meroterpenoids (16NPR26), isolation, biological properties, and synthesis of dimeric pyranonaphthoquinones (16EJO5778), and peroxide and peroxide-derived polyketide metabolites from marine sponges (16NPR861). Late-stage convergent annulation reactions (16T3345) and rhodium-catalyzed annulation reactions of arenes with alkynes via weak chelation-assisted CdH activation (16CC2872) for the synthesis of several natural six-membered oxacycles have also been reviewed. New approaches for the synthesis of naturally occurring bioactive pyran derivatives have appeared. Different routes have been established for the total synthesis of tetrahydropyran-containing natural compounds brevisamide (16EJO2300, 16JOC3799), (±)-centrolobine (16SL2221), (−)-clavosolide A (16AGE2498), (+)-decarestrictine L (16TL4368), decytospolide A, B, and their C-3 epimers (16S765), goniodomin A (16JOC2213), herboxidiene (16OBC6212), irciniastatins (16JOC1930), (−)-lasonolide A (16JA11690), (−)-luminacin D (16JOC3818), (−)-mandelalide A (16JA770, 16JA3675), isomandelalide A (16JA770), thailanstatin A (16JA7532); of the 2H-pyran- 2-ones sibirinone, (E)-6-(pent-1-en-1-yl)-2H-pyran-2-one and (E)-6- (hept-1-en-1-yl)-2H-pyran-2-one (16JOC10357); of the 5,6-dihydropyran- 2-one derivatives cryptomoscatone F1 (16S1561), cryptorigidifoliol B (16TL2100), cryptorigidifoliol E (16S4213), 8-methoxygoniodiol (16S4300), pectinolides A, C, and H (16HCA247); and of the tetrahydropyran-2-one derivatives (−)-(S)-goniothalamin and (−)-leiocarpin (16SC187), helicascolides A, B, and C (16AGE5765), isodaphlongamine H (16AGE2577), and (−)-malyngolide and its C-5 epimer (16HCA267).